Tingkat Kemampuan Komunikasi Matematis pada Materi Sistem Persamaan Linear Tiga Variabel - Ulum, Achmad Miftachul (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2025)
Mathematics learning requires students to be able to master various mathematical abilities. Mastery of these mathematical abilities aims to make it easier for students to receive information during learning. mathematics as language, which means that mathematics can be used in communication between students. In this case, mathematical communication skills must be possessed by students, in order to make it easier for them to solve math problems. The purpose of this study was to determine the level of mathematical communication skills on the material of linear equations of three variables. The approach used is descriptive qualitative. The instruments used were mathematical communication skills questions, and interview guidelines. Researchers used triangulation techniques to strengthen the data obtained. The data that has been obtained is analyzed using the Miles and Hubermen method, which has four stages. The results of this study are that students who have low mathematical communication skills tend to master only one indicator of mathematical communication skills. Learners who have moderate mathematical communication skills tend to master two indicators of mathematical communication skills. Learners who have high mathematical communication skills, tend to have mastered all indicators of mathematical communication skills. Suggestions from this study are, that further researchers try to do research on mathematical communication skills.